PRODUKTIVITAS DAN MUSIM PENANGKAPAN IKAN DOMINAN MENGGUNAKAN PURSE SEINE DI PELABUHAN PERIKANAN PANTAI TAMPERAN, PACITAN - Lilik Muzayanah; Mohammad Imron; Mulyono Sumitro Baskoro (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
Purse seine fishing significantly contribute to fish production at Tamperan fishing port, Pacitan. However decreasing production trend is threatening as a result of overfishing and poor information about fishing seasonal patterns. Purse seine at Tamperan port mostly catch highly valued pelagic fish. Those fish are popular in the region and caught its respective seasonal patterns. The research aims at calculating the fishing productivity and identifying the seasonal pattern of the major targeted species of purse seine based at the Tamperan fishing Port, Pacitan. The research was conducted by interviewing 18 fishers, head of fish auction center and some offers of Tamperan fishing port. Data collection incorporated catch production, types of fish, fishing trips and other data. Productivity was calculated according to KEPMEN N0.61/2014 while fish season patterns were projected using time series and moving average methods. During the last 5 years the fish production landed at PPP Tamperan were skipjack, mackerel scad, and tuna. The number of productions decreased as well as the level of productivity. Factors affecting productivity included the number of crew members, fishing trips, gross tonnage, engine, and net length. Purse seine productivity based on the number of fishing trips (ton/trip) has increased while others have decreased. According to the fish seasons, the best period to conduct purse seine operations in Pacitan Regency are in March, May-September (skipjack), December-February, April-May (mackerel scad), and January-April, July, August (tuna). Keywords: Purse seine, productivity, dominant fishing season, Pacitan.